Influence of football match time-motion parameters on recovery time course of muscle damage and jump ability - de Hoyo, M.; Cohen, D. D.; Sañudo, B.; Carrasco, L.; Álvarez-Mesa, A.; Del Ojo, J. J.; Dominguez-Cobo, S.; Mañas, V.; Otero-Esquina, C. (Journal of Sports Sciences, 2016)
We analysed the time course of recovery of creatine kinase (CK) and countermovement jump (CMJ) parameters after a football match, and correlations between changes in these variables and match time-motion parameters (GPS-accelerometry) in 15 U-19 elite male players. Plasma CK and CMJ height (CMJH), average concentric force (CMJCON) and average eccentric force (CMJECC) were assessed 2 h before and 30 min, 24 h and 48 h post-match. There were substantially higher CK levels 30 min, 24 h and 48 h (ES: 0.43, 0.62, 0.40, respectively), post-match. CMJECC (ES: -0.38), CMJH (ES: -0.35) decreased 30 min post, CMJCON (ES: -0.35), CMJECC (ES: -0.35) and CMJH (ES: -1.35) decreased 24 h post, and CMJCON (ES: -0.41) and CMJH (ES: -0.53) decreased 48 h post. We found correlations between distance covered at velocities =21 km/h and changes in CK at 24 h (r = 0.56) and at 48 h (r = 0.54) and correlations between CK and distance covered >14 km/h (r = 0.50), accelerations (r = 0.48), and decelerations (r = 0.58) at 48 h. Changes in CMJCON 30 min and 24 h post (both r = -0.68) correlated with impacts >7.1·G. Decelerations >2 m · s-2 correlated with changes CMJCON (r = -0.49) at 48 h and CMJECC (r = -0.47) at 30 min. Our results suggest that match GPS-accelerometry parameters may predict muscle damage and changes in components of neuromuscular performance immediately and 24-48 h post-match.